2019
DOI: 10.1002/adsc.201801410
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Hydroxyl‐Enabled Cycloaddition of Azides and Alkynes

Abstract: A novel iridium-catalyzed hydroxyl-enabled cycloaddition of azides and alkynes has been developed. In the presence of catalytic amount (2 mol%) of [Ir(cod)Cl] 2 , the 2-alkynyl phenols would engage in a regioselective cycloaddition with various azides for rapid access to diverse triazoles, and the hydroxyl group acts as directing group to enable this reaction. The process is featured mild and biocompatible reaction condition with the achievement of brevity and diversity. Furthermore, the hydroxyl group offers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…In both cases, the reactions are fully regioselective, but mm concentrations of the reagents are required,w hich so far limits their use for chemical and cell biology applications. [44]…”
Section: Copper(i)-promoted Azide-alkyne Cycloaddition (Cuaac)mentioning
confidence: 99%
“…In both cases, the reactions are fully regioselective, but mm concentrations of the reagents are required,w hich so far limits their use for chemical and cell biology applications. [44]…”
Section: Copper(i)-promoted Azide-alkyne Cycloaddition (Cuaac)mentioning
confidence: 99%
“…[39] In 2019, Cui and coworkers demonstrated that by introducing an ortho hydroxyl group into the aryl ring, IrAAC reactions of them were enormously promoted, regioselectively affording trisubstituted triazoles 56 in up to 96% yield (Scheme 29). [46] Since the C � C Cui et al reported that IrAAC is suitable for 1-alkynyltriazenes 57 as well, in which the triazenyl group is thought to be crucial in determining the regioselectivity (Scheme 30). [47] Notably, the formed 5-triazenyltriazoles 58 could be easily converted into 5-amino triazoles 59, which could be further decorated to provide a variety of functionalized triazoles (60-62 for instance).…”
Section: Ira I Acmentioning
confidence: 99%
“…[42,52] Cui et al reported the RhAAC reaction of 2-(phenylethynyl)phenol to afford triazole 73 with absolute regiocontrol (Scheme 34b). [46] Related plausible mechanisms to elucidate the regiocontrol in above cases were shown in Scheme 35. The electronic effect- From the cases listed in this section we can see that both the alkyne scope and mechanism of RhA I AC are similar to IrA I AC.…”
Section: Rha I Acmentioning
confidence: 99%
See 1 more Smart Citation
“…The same catalytic system also works for the C-S coupling of aryl halides and sulfinate salts. [68] Scheme 29. Thioetherification via EDA complex formation.…”
Section: Electron Donor-acceptor Complexesmentioning
confidence: 99%